(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The aim of this study is based on knowledge of mimars to explain and show of fundamental components of muqarnas, creation method, and methodology. Furthermore, to better explain the process of muqarnas creation the author analyzed some of the historical scrolls from Tashkent and demonstrated how to rebuild the 3D design of muqarnas based on 2D planes. To find the answer, the authors will attempt to discover the essence of the Muqarnas. First, the preliminary definitions of this craft will be outlined, after which its development will be traced. Thereafter, a new discourse on Islamic Architecture parallel to the studies of Muqarnas will be initiated. At this point, Patkâné will be presented as an early origin of the Muqarnas. Comparing these two crafts leads to the early ideas of prefabrication and modularization. Specific studies on the proposed hypothesis are based on recognition of the traditional methods in areas of design, calculation, and construction of the Muqarnas in Persian and Islamic Architecture